The Microbiome in Male Reproduction and Sexual Function: From the Gut-Testis Axis to Clinical Applications (Vietnam Journal of Community Medicine, 2026)
The microbiome is increasingly recognized as an important regulator of male reproductive and sexual health through immune, metabolic, and endocrine pathways. This narrative review aims to summarize current evidence regarding the role of gut microbiota and the male reproductive tract microbiome (androbactome) in spermatogenesis, semen quality, testosterone regulation, and male sexual dysfunction, particularly erectile dysfunction.Relevant literature including review articles, observational studies, randomized controlled trials, Mendelian randomization analyses, and contemporary guidelines published mainly between 2022 and 2026 was analyzed. Current evidence suggests that microbial dysbiosis is associated with impaired spermatogenesis, abnormal semen parameters, increased sperm DNA damage, chronic low-grade inflammation, and endothelial dysfunction related to erectile dysfunction. Emerging Mendelian randomization studies also support potential causal relationships between specific gut microbial taxa and the risk of erectile dysfunction. In addition, probiotic and synbiotic interventions have shown preliminary potential in improving selected semen parameters and oxidative stress markers in certain patient populations.However, the available evidence remains heterogeneous and is still largely derived from observational studies and preclinical models. At present, the microbiome should be considered a complementary biological dimension in andrology rather than a standardized diagnostic or therapeutic target. Lifestyle and metabolic optimization remain the most evidence-based strategies to support a healthy microbiome in men with infertility or sexual dysfunction.